2007
DOI: 10.1073/pnas.0709387104
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of EmrE supports dual topology model

Abstract: EmrE, a multidrug transporter from Escherichia coli, functions as a homodimer of a small four-transmembrane protein. The membrane insertion topology of the two monomers is controversial. Although the EmrE protein was reported to have a unique orientation in the membrane, models based on electron microscopy and now defunct x-ray structures, as well as recent biochemical studies, posit an antiparallel dimer. We have now reanalyzed our x-ray data on EmrE. The corrected structures in complex with a transport subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
277
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(305 citation statements)
references
References 41 publications
26
277
1
1
Order By: Relevance
“…These results are in agreement with cross-linking analysis in this detergent suggesting destabilization of the EmrE dimer (21). They are also consistent with the conclusion of Chen et al (17) that the crystal structure of apo EmrE in this detergent is likely to be misfolded. Accessibility Profiles Identify Transmembrane Segments and Water-accessible Regions-The orientation and boundaries of EmrE transmembrane helices were deduced from measurement of collision frequency of each spin-labeled site with paramagnetic probes that are either lipid-soluble (molecular oxygen) or water-soluble (NiEDDA) (24,33).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with cross-linking analysis in this detergent suggesting destabilization of the EmrE dimer (21). They are also consistent with the conclusion of Chen et al (17) that the crystal structure of apo EmrE in this detergent is likely to be misfolded. Accessibility Profiles Identify Transmembrane Segments and Water-accessible Regions-The orientation and boundaries of EmrE transmembrane helices were deduced from measurement of collision frequency of each spin-labeled site with paramagnetic probes that are either lipid-soluble (molecular oxygen) or water-soluble (NiEDDA) (24,33).…”
Section: Resultssupporting
confidence: 92%
“…Comparison of the EPR Parameters with the Structure of the TPP ϩ -bound EmrE-As noted above, there are multiple EmrE regions where the EPR parameters of the apo intermediate deviate from the expected environments in the crystal structure (17) and a model based on the EM structure (35). These deviations may reflect the conformational changes upon TPP ϩ FIGURE 6.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The claim for an antiparallel topology was supported by a reinterpretation of the electron density maps of two-dimensional crystals of EmrE that showed that parts of the structure are related by quasisymmetry (37). A C␣ model of the transmembrane region was constructed by considering the evolutionary conservation pattern of each helix (34) and was supported by a re-evaluation of the data published in the retracted papers (38). Our own work demonstrates that dimers with parallel topology are functional and the functionality of antiparallel dimers remains to be established (36,39,40).…”
Section: Discussionmentioning
confidence: 95%
“…Proteins with dual topology are known to have weak signals (net differences in charged amino acids next to membrane boundaries involved in determining membrane topology) adjacent to transmembrane domains (30). Interestingly, for at least one known bacterial protein, the relative proportions of the opposing topological orientations depend on growth conditions (10,33), raising the possibilities that (i) the ratio between the two orientations may not always be unity, and (ii) post/co-translational modification(s) may alter the net charges at critical membrane boundary regions of the protein sequence so as to control the relative proportions of the two alternative orientations depending on the prevailing activity of protein modifying enzymes. If these considerations can be extrapolated to DGAT1, they may explain our previous observations that the relative amounts of overt and latent DGAT activity in the ER of rat liver (which will be dependent on the relative distribution of DGAT1 activity as this accounts for the majority of the overt DGAT activity) are capable of modulation by physiological state and by hypolipidemic drug treatment (6).…”
Section: Discussionmentioning
confidence: 99%